2017
DOI: 10.1152/ajprenal.00401.2016
|View full text |Cite
|
Sign up to set email alerts
|

ENaC activity in the cortical collecting duct of HKα1 H+,K+-ATPase knockout mice is uncoupled from Na+ intake

Abstract: Modulation of the epithelial Na channel (ENaC) activity in the collecting duct (CD) is an important mechanism for normal Na homeostasis. ENaC activity is inversely related to dietary Na intake, in part due to inhibitory paracrine purinergic regulation. Evidence suggests that H,K-ATPase activity in the CD also influences Na excretion. We hypothesized that renal H,K-ATPases affect Na reabsorption by the CD by modulating ENaC activity. ENaC activity in HKα H,K-ATPase knockout (HKα) mice was uncoupled from Na inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…We also found that MRS2768 decreases ENaC activity in isolated split-open tubules, suggesting one possible cause for this increase in Na ϩ excretion. These findings are in agreement with similar previous observations that 1) ATP and UTP decrease ENaC activity in native principal cells via P2Y 2 receptor-G q signaling (6,25,26,30,33,47); 2) selective P2Y 2 receptor agonism with INS45973 decreases blood pressure, increases Na ϩ excretion, and increases fractional excretion of fluid and Na ϩ in wild-type, but not P2Y 2 receptor knockout, mice; and 3) INS45973 is without effect on GFR in both wild-type and knockout mice (39,40). The effects of both MRS2768 in the present study and INS45973 in this prior study on renal excretion mirror those of the ENaC inhibitor amiloride: they promote a natriuresis without an accompanying change in GFR.…”
Section: Discussionsupporting
confidence: 94%
“…We also found that MRS2768 decreases ENaC activity in isolated split-open tubules, suggesting one possible cause for this increase in Na ϩ excretion. These findings are in agreement with similar previous observations that 1) ATP and UTP decrease ENaC activity in native principal cells via P2Y 2 receptor-G q signaling (6,25,26,30,33,47); 2) selective P2Y 2 receptor agonism with INS45973 decreases blood pressure, increases Na ϩ excretion, and increases fractional excretion of fluid and Na ϩ in wild-type, but not P2Y 2 receptor knockout, mice; and 3) INS45973 is without effect on GFR in both wild-type and knockout mice (39,40). The effects of both MRS2768 in the present study and INS45973 in this prior study on renal excretion mirror those of the ENaC inhibitor amiloride: they promote a natriuresis without an accompanying change in GFR.…”
Section: Discussionsupporting
confidence: 94%
“…Mironova et al observed that ENaC activity was not appropriately downregulated in HKA1-null mice on a high-Na + diet, leading to Na + retention and an impaired dipsogenic response. Urinary ATP was lower in HKA1-null mice on a high-Na + diet, relative to WT mice on the same diet, which may explain why ENaC was less inhibited in the KO mice (46).…”
Section: Interactions Between Principal Cells and Type A Cellsmentioning
confidence: 98%
“…conditions (46). Mironova et al observed that ENaC activity was not appropriately downregulated in HKA1-null mice on a high-Na + diet, leading to Na + retention and an impaired dipsogenic response.…”
Section: Interactions Between Principal Cells and Type A Cellsmentioning
confidence: 99%